2021
DOI: 10.1093/bjsw/bcaa228
|View full text |Cite
|
Sign up to set email alerts
|

Poverty Awareness: Development and Validation of a New Scale for Examining Attitudes regarding the Aetiology and Relational–Symbolic Aspects of Poverty

Abstract: This study describes the development and validation of a new Poverty Awareness Scale (PAS). Existing scales of attitudes towards poverty focus on poverty’s aetiology, leaving other notions regarding poverty underexplored. Our new scale is based on the key role that relational–symbolic aspects of poverty play in current critical poverty knowledge and adds the examination of these aspects. The scale was distributed to 127 social workers and social work students before and after six different poverty-aware course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Studies have provided evidence that following the training, participants tended to understand poverty through structural rather than individualistic explanations and became more aware of the connections between poverty and Otherness (Weiss‐Dagan and Krumer‐Nevo, 2022). Other studies found that after receiving PAP training, social workers engaged in the practice of actualization of rights (Weiss‐Gal, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have provided evidence that following the training, participants tended to understand poverty through structural rather than individualistic explanations and became more aware of the connections between poverty and Otherness (Weiss‐Dagan and Krumer‐Nevo, 2022). Other studies found that after receiving PAP training, social workers engaged in the practice of actualization of rights (Weiss‐Gal, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A study that examined social workers' attitudes toward poverty found that the courses transformed conservative attitudes into more structural and critical ones (Weiss‐Dagan and Krumer‐Nevo, 2022). In another study, social workers attested that their worldviews regarding their role as social workers changed, and reported that they had gained knowledge and tools that enabled them to reach out and establish close and beneficial relationships with service users who had previously been beyond their reach (Ben‐Rabi, 2019).…”
Section: The Pap Training Modelmentioning
confidence: 99%
“…All the studies that examined social workers' attitudes found that they developed a degree of critical analysis during the PAP training and ongoing supervision, e.g., [31,33]. A quantitative study that investigated the attitudes of 127 social workers before and after PAP training courses found significantly higher scores in the perception of poverty as structural and in acknowledging the relational and symbolic aspects of living in poverty at T2 [31].…”
Section: Social Workers' Attitudes Toward Poverty and People In Povertymentioning
confidence: 99%
“…All the studies that examined social workers' attitudes found that they developed a degree of critical analysis during the PAP training and ongoing supervision, e.g., [31,33]. A quantitative study that investigated the attitudes of 127 social workers before and after PAP training courses found significantly higher scores in the perception of poverty as structural and in acknowledging the relational and symbolic aspects of living in poverty at T2 [31]. In P2, 33 social workers were interviewed before, during, and after the three-year pilot phase of the program, showing that they developed structural and holistic interpretations of service users' stories that connected closely to the relational and symbolic meanings of poverty: "[Previously] I thought that the children should leave the house .…”
Section: Social Workers' Attitudes Toward Poverty and People In Povertymentioning
confidence: 99%